A Decision Support Tool for Stakeholder Engagement in Sustainable Land Management Using the WEFE Nexus: A Simulation for the Aral Sea Basin Stakeholders - Verbist, Joren; Akramkhanov, Akmal (Springer, Cham, 2025)
Land degradation affects billions of people, particularly in developing countries, exacerbating poverty and climate change. Sustainable Land Management (SLM) practices offer solutions, but decision-making is complex and requires considering multiple stakeholders. This paper proposes a Decision Support Tool (DST) based on Multi-Criteria Decision Making (MCDM) and the Water-Energy-Food-Ecosystems (WEFE) Nexus framework. The DST integrates WEFE sector stakeholders’ perspectives through the Best–Worst Method (BWM), facilitating informed land management choices. A case study in the Aral Sea Basin illustrates the DST’s applicability, demonstrating how four WEFE simulated stakeholders might prioritize SLMs. While the DST provides valuable insights, it requires careful consideration of contextual factors and encourages (deeper) sectoral stakeholder dialogue. Overall, the DST serves as a practical tool to enhance WEFE sectors stakeholders’ inclusivity and improve decision-making in SLM, offering potential solutions to mitigate land degradation and its associated socio-economic challenges.